THE ANALYSIS OF ECONOMIC ACTIVITIES OF WASTE RECYCLING SCAVENGERS IN TERJUN URBAN VILLAGE MEDAN MARELAN SUB-DISTRICT - Ashri Maulida; Mr Arwansyah (Quantitative Economics Journal, 2019)
Waste management can reduce negative impacts on the environment, even if garbage is properly managed has economic value that is promising. Recycling is one of the businesses on waste minimization at the source of generation such as the Household and the Market must be addressed in the Final Disposal. more effective. This study aims to determine the economic value for the garbage collector. Does this activity has to be developed prosfek? This research is also expected to assist the government in formulating policies, among others, (1) the alleviation of poverty; (2) to determine the characteristics of the waste; (3) to determine the value of the sale of inorganic waste; (4) the value of marketing margin recycling efforts. For that determined the variables expected to affect the economy of scavengers that radius trash pickup, work experience, gender and the mode of transport used scavengers. Primary data were collected from households, markets, scavengers, agents of small and large agents inorganic waste recycling business. Descriptive analysis methods include behavioral analysis, analysis of the characteristics of household rubbish, garbage value analysis of inorganic and margin analysis. Linear Regression analysis method (Ordinary Least Square) to see the effect of these variables on the path towards economic scavengers Household and Final Disposal. The results of this study indicate that the variable radius waste pick-up and work experience scavengers positive effect on the economic value of the landfill scavengers either on line or lines of Household. Trash aqua glass, waste paper HVS, copper and garbage bins clear glass bottle is a kind of inorganic waste which has a high sales value per kilogram. Household garbage Marketing paths more effectively and profitably than the path landfill. Household scavenger pathway is more prosperous than landfill scavengers path. Public awareness is still low in maintaining the environment. Development activities in the Garbage Bank program has prospects for poverty reduction.